PERGESERAN KEKUASAAN BANGSAWAN JAWA INDONESIA: SEBUAH ANALISIS WACANA KRITIS - Sailal Arimi (Jurnal Masyarakat dan Budaya, 2008)
Adopting Critical Discourse Analysis (CDA) approach, this paper offers a model of sociolinguistic study on identity of power in the case of Javanese local gentry (nobleman). The analysis strongly confirmed Soemardjan’s (1981) thesis that the Javanese local gentry did not any longer hold powers of economy and politics towards their people. Their power has shifted to the unpowerful area of culture. Such power shift has given an impact to breaking traditional structure of Javanese society. A conclusion drawn from the analysis undoubtedly proposes a critical thesis that the structure of Javanese society as argued by Koentowijoyo (2004) as consisting of the Sultanate, priyayi (local gentry), and kawula (the people) should have been reconsidered. In this paper, I propose that the modern structure of Javanese society should consist of only the Sultanate and the people. Until this time, the Sultan does still play his role as administration.